2021
DOI: 10.1186/s10086-021-01942-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of microwave pretreatment on drying of 50 mm-thickness Chinese fir lumber

Abstract: Low permeability of wood causes problems during drying of timber. This study evaluated the effects of microwave (MW) pretreatment on the conventional drying behavior and mechanical damages of Chinese fir lumber. MW pretreatment of lumber was performed at applied MW energy of 43 kWh/m3, and then, the samples were dried in a laboratory drying kiln. The results showed that the drying rate was effectively increased after MW pretreatment. The moisture content (MC) deviation in thickness and residual stress indexes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 18 publications
3
34
0
Order By: Relevance
“…MW treatment has become more popular in the field of heat-treated wood products [4], and it has been used for a variety of purposes, including wood drying, [12][13][14][15], improvement of fluid permeability [7,8,[16][17][18][19], and impregnation by preservative agents [18,20]. Torgovinikov and Vinden [21] explained that hardwood species tend to take longer in the drying process.…”
Section: Introductionmentioning
confidence: 99%
“…MW treatment has become more popular in the field of heat-treated wood products [4], and it has been used for a variety of purposes, including wood drying, [12][13][14][15], improvement of fluid permeability [7,8,[16][17][18][19], and impregnation by preservative agents [18,20]. Torgovinikov and Vinden [21] explained that hardwood species tend to take longer in the drying process.…”
Section: Introductionmentioning
confidence: 99%
“…Microwave pre-treatment may significantly reduce the formation of internal/ honeycombing and surface checking in drying [42]. The experiment of Weng et al witnessed the increase in the drying rate caused by microwave pre-treatment [43]. In Figure 2, it can be clearly seen that the drying time of the microwave pre-treatment sample is shorter than that of the control sample.…”
Section: Wood Drying Defects and Drying Stressmentioning
confidence: 95%
“…* means significant at 0.05 level, -means not significant at 0.05 level. Values of drying uniformity are standard deviations of the final MC[43].…”
mentioning
confidence: 99%
“…Various studies on microwave treatment have been reported in the field of wood modification. The main purpose of applying microwave treatment in wood modification is to improve the permeability [1,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Weng et al [17] reported that, after pretreatment of Chinese fir lumber using a microwave, pit membranes were damaged, ray parenchyma cells and tracheids were detached, and micro-cracks in the radial section were observed. This treatment contributed to shortening of the drying time due to formation of new pathways for moisture transfer.…”
Section: Introductionmentioning
confidence: 99%